(untitled) (Research, Society and Development, 2022)
Objective: to identify, through an integrative literature review, the effects of intensive physical therapy on the motor function of patients hospitalized for COVID-19. Methodology: This study was characterized as an integrative literature review, with a descriptive and qualitative approach, which took place through the survey of scientific articles that were related to the objective of the study. Articles related to the proposed theme were included, published between the years 2019 to 2022, available in full, without language restriction; in addition to theses, dissertations and monographs. Results: A total of 596 articles were found, in which all had their titles and abstracts read, after that, 532 articles were excluded for not meeting the eligibility criteria, leaving 64 articles that were carefully read in full, after full reading, 5 articles were selected to be tabulated and characterized, meeting the PICO strategy. Final considerations: evidence indicates that physiotherapy has an important effect on maintaining the quality of life, functionality, autonomy and independence of patients undergoing hospitalization for the new coronavirus. The main physiotherapy strategies applied to these patients were mobilization protocols and/or early therapeutic exercises, aerobic exercises and post-COVID-19 physiotherapeutic follow-up, so that the sequelae of this post-hospitalization pathology are minimized and/or treated.